An Examination of the Digital Parenting Profiles in Turkey - Yaman, Fatih; Yurdakul, Işıl Kabakçı; Akbulut, Yavuz; Dönmez, Onur (Springer, 2022)
Internet use among children is increasing. This requires parents to develop digital parenting competencies as they are responsible for their children's well-being. In the current study the digital parenting self-efficacy perceptions of Turkish parents are examined with regard to the parental role, educational status, age, number of children, and Internet use experiences. Data were collected from a stratified sample of 7150 Turkish parents (i.e., only the mother or father in each family) from twenty-six provinces through the Digital Parenting Self-Efficacy Perception Scale. Descriptive statistics, comparison tests, and cluster analysis were used to analyze the data. The findings reveal that the participants' perceived digital parenting efficacy is high, and that perceptions change in terms of the parental role, educational status, age, number of children, and the Internet use experience.
Keywords: Digital parenting; self-efficacy; gender; Internet use; Internet Use; Association; Literacy; Children; Styles